The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1371/journal.pone.0200168
|View full text |Cite
|
Sign up to set email alerts
|

Pregnant women co-infected with HIV and Zika: Outcomes and birth defects in infants according to maternal symptomatology

Abstract: BackgroundZika virus (ZIKV) was first isolated in Uganda in 1947. In Brazil, the first reported case of ZIKV infection was in May 2015. Additionally, dengue (DENV) is endemic and there has been a recent outbreak of chikungunya (CHIKV). Since the clinical manifestations of different arboviral infections (AI) can be similar, definitive diagnosis requires laboratory testing.ObjectivesTo determine the prevalence of ZIKV, DENV, and CHIKV infections in a Brazilian cohort of HIV-infected pregnant women, to assess cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…The variation in the number of pregnant women in the studies ranged from 28 [ 19 ] to 19,963 [ 39 ]. The overall studies were conducted in the Americas: Brazil [ 25 , 26 , 29 , 33 , 34 , 38 ], Puerto Rico [ 18 ], United States of America (USA) [ 19 , 21 , 22 , 24 , 35 , 37 , 40 ], Peru [ 30 ], French territories of the Americas: French Guiana, Guadeloupe and Martinique [ 20 , 36 ] and Colombia [ 23 , 27 , 28 , 39 ]. Quality scores for the studies are available in S3 Table .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The variation in the number of pregnant women in the studies ranged from 28 [ 19 ] to 19,963 [ 39 ]. The overall studies were conducted in the Americas: Brazil [ 25 , 26 , 29 , 33 , 34 , 38 ], Puerto Rico [ 18 ], United States of America (USA) [ 19 , 21 , 22 , 24 , 35 , 37 , 40 ], Peru [ 30 ], French territories of the Americas: French Guiana, Guadeloupe and Martinique [ 20 , 36 ] and Colombia [ 23 , 27 , 28 , 39 ]. Quality scores for the studies are available in S3 Table .…”
Section: Resultsmentioning
confidence: 99%
“…The criteria for ZIKV infection followed that recommended by the Center for Disease Control and Prevention (CDC) [ 41 ]: positive RT-PCR in serum or urine or IgM for ZIKV by the enzyme-linked immunosorbent assay (ELISA) method, including the PRNT for the differential diagnosis with other arboviruses. In 11 cohorts, only pregnant women with positive RT-PCR for ZIKV in serum or urine were included [ 23 , 25 – 30 , 33 , 34 , 36 , 39 ] and ten cohorts included pregnant women with RT-PCR confirmed infection for ZIKV in serum or urine and those with probable infection with IgM measurement with PRNT for ZIKV [ 18 22 , 24 , 35 , 37 , 38 , 40 ]. In nine studies, only symptomatic pregnant women were included [ 23 , 25 , 27 29 , 33 , 34 , 36 , 40 ], in the other 12 studies, both symptomatic and asymptomatic pregnant women were included.…”
Section: Resultsmentioning
confidence: 99%
“…Traveller/non-traveller populations: In this update, we found further evidence that congenital abnormalities occurred in infants born to women travellers returning from ZIKV-affected areas and women remaining in those areas. In total, 25 publications report on 272 congenital abnormalities due to ZIKV infection in travellers 27, 29, 30, 32, 34, 36, 38, 42, 45, 56, 58, 61, 89, 94, 98, 109, 117, 122, 123, 137, 140, 151, 153, 166, 173 , with 109 publications reporting congenital abnormalities due to ZIKV in 2652 non travellers 2426, 28, 31, 33, 35, 37, 3941, 43, 44, 4648, 50, 51, 54, 57, 60, 6279, 81, 8385, 87, 88, 9093, 95– 97, 100, 101, 104– 106, 110113, 115, 116, 118, 119, 121, 124135, 142147, 149, 152, 154, 156164, 167, 168, 171, 172, 175180, 182, …”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have revealed a significant increase in the number of HIV-ZIKV co-infected individuals reported in endemic areas in America [ 20 23 ] and Africa [ 24 ]. Additionally, the National Institute of Health (NIH) initiated an international, multisite clinical study, “Prospective Cohort Study of HIV and ZIKV in Infants and Pregnancy” (HIV ZIP; ClinicalTrials.gov, # NCT03263195) to register 2,000 pregnant women for the purpose of investigating ZIKV/HIV co-infection in the United States, Brazil, and Puerto Rico.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the National Institute of Health (NIH) initiated an international, multisite clinical study, “Prospective Cohort Study of HIV and ZIKV in Infants and Pregnancy” (HIV ZIP; ClinicalTrials.gov, # NCT03263195) to register 2,000 pregnant women for the purpose of investigating ZIKV/HIV co-infection in the United States, Brazil, and Puerto Rico. Further studies suggest that although a high prevalence (72%) of ZIKV among 219 HIV-infected pregnant women was reported [ 20 , 23 ]; their clinical presentation suggested a mild disease with a rapid and complete recovery. However, the fetuses of these women were often born with significant abnormalities, similar to those described previously in the children of women without HIV infection [ 25 ] and fetal demise would often occur [ 20 ].…”
Section: Discussionmentioning
confidence: 99%